Penerapan Media Pembelajaran Interaktif Quizwhizzer dengan Metode Diferensiasi Pembelajaran untuk Meningkatkan Hasil Belajar Siswa di SMK Muhammadiyah 2 Kuningan - Riana, Fadil Eka; Setiawan, Dena Latif (Indo-MathEdu Intellectuals Journal, 2024)
This research aims to improve student learning outcomes in Computer Fundamentals subjects by using the learning differentiation method using quizwhizzer interactive media. This study uses the pre-experiment method with the research design used is "One Gruop Pretest-Posttest Design". The sample was 16 people consisting of 14 men and 3 women in class X Computer Engineering, Network Engineering, Data Collection Questions/Tests (Pretest-Posttest) and Quesioner (Pretest-Posttest). Data analysis was carried out on the results of the pretest and posttest which were tested using the t-test. The results of the study showed that there was a difference in the learning outcomes of students who were taught using conventional learning methods and the learning outcomes of students who were taught using quizwhizzer learning media using the differentiation method in the Computer Basics material of class X TKJ at SMK Muhammadiyah 2 Kuningan, this can be seen from the results of hypothesis testing using the t-test obtained from the results of the calculation of the hypothesis test (t-test) the posttest score was known to be the average score 60.75 while the pretest with an average of 48.37 so that it is known that the increase in the posttest learning outcome score is greater than 12.38 compared to the pretest learning outcome score. So that it can be stated that there is a significant difference in the increase in learning outcomes in the pretest and posttest